PENGARUH PEMBERIAN SUPLEMENTASI VITAMIN B PADA PENCEGAHAN DAN PENYEMBUHAN STROKE - Peter; Felisia; Joshua Ashley; Tonam (Neurologi Manado, 2020)
Stroke is the second leading cause of death and the third leading cause of disability worldwide. Approximately 85-90% of stroke are ischemic. Ischemic stroke is characterized by a reduction in cerebral blood flow resulting in poor glucose and oxygen delivery to the brain, leading to neuronal cell death. Time until treatment is critical. Rapid injury progression, neurovascular management, limitation to the access of recombinant tissue plasminogen activator (rtPA) for thrombolysis, anticoagulation and antiplatelet intervention, and neuroprotection all affect outcome. Supplementation with vitamin B have been proved to reduce the risk of stroke and improve post-stroke recovery.